2011
DOI: 10.3184/146867811x13021847366179
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modelling of the Fenton-Like Oxidation of Maleic Acid Using a Heterogeneous Modified Polyacrylonitrile (Pan) Catalyst

Abstract: A kinetic model has been developed that expresses the oxidation of maleic acid in solution using a novel modified (polyacrylonitrile) PAN catalyst=hydrogen peroxide system. The novel modified PAN catalyst contains immobilised Fe 3 þ and its reaction with hydrogen peroxide is thought to generate reactive hydroxyl radicals according to Fenton's reaction as well as another active iron oxo species. The model takes into account the presence of both hydroxyl radicals and active iron oxo species as well as hydroperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…The possible reaction mechanism of H 2 O 2 decomposition by complex 1 is given below.In the possible proposed reaction mechanism, eq 5 was an intermediate of the decomposition of H 2 O 2 by complex 1 . 57…”
Section: Resultsmentioning
confidence: 99%
“…The possible reaction mechanism of H 2 O 2 decomposition by complex 1 is given below.In the possible proposed reaction mechanism, eq 5 was an intermediate of the decomposition of H 2 O 2 by complex 1 . 57…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been previously shown that EF is the least effective electrochemical process (compared with direct anodic oxidation at BDD or indirect oxidation by electro-generated active chlorine) for the removal of AO7 because of the formation of recalcitrant by-products. [42] According to the literature, the main relevant by-products are hydroquinone, oxalic and maleic acids which remain in the solution for very long times during EF process. [19,42]…”
Section: Electrofenton Treatment Of Aqueous Solutions Of Formic Acid Oxalic Acid and Acid Orangementioning
confidence: 99%
“…One of the materials successfully used is a surface functionalised nanocoated modied polyacrylonitrile (MPAN) bre in the form of a mesh. [3][4][5][6] The PAN mesh was modied to introduce surface functionalisation by amidoximation with a mixture of hydrazine and hydroxylamine at alkaline pH to allow surface complexation with iron(III) sulphate salt. 3,[7][8][9] This introduces groups such as amidoxime, amidrazone, amide and carboxylate onto the bres of the PAN mesh.…”
Section: Introductionmentioning
confidence: 99%
“…When used with hydrogen peroxide at pH 3, the catalyst is seen to give excellent oxidation of organic pollutants in wastewater. [3][4][5][6] The catalyst degrades pollutants via a heterogeneous Fentonlike mechanism (eqn (1) and (2)), which is known to be slightly slower in comparison to a homogenous Fenton's degradation. However, as the iron in this study is chelated to a PAN support, the amount of iron leaching and hence secondary pollution is reduced drastically.…”
Section: Introductionmentioning
confidence: 99%